The Role of the Economy in the Development of the Country - M., Narinov; Ashurova, Z. Sh. (International Journal on Orange Technologies, 2023)
This article provides starting information to shape the economy in our country, bring it into your lifestyle and increase your financial literacy. Currently, the knowledge necessary for our entrepreneurs is provided in detail in the article about this financial knowledge.